Pengaruh Pembelian Melalui Aplikasi Go-Food Terhadap Penjualan Di Jelly Potter Cabang Jaya Sampurna - Wulan Julliyanti; Syifa Pramudita Faddilla (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This study aims to determine how much influence the Go-Food application has on sales at Jelly Potter Jayasampurna Branch. This analysis uses the independent variable, namely Go-Food and the dependent variable, namely sales at the Jelly Potter business. The sample of this research is consumers who have made purchases through the Go-Food application, business owners who have made buying and selling transactions on the Gojek application. Data collection was carried out by collecting primary data with observation techniques, documentation, questionnaires, interviews and literature studies. The statistical method uses the Average Test of Two Dependent Populations, namely to test the average difference between two groups of data that are dependent or interrelated. The results of this study indicate that the purchasing variable through the Go-Food application (X) has a significant effect on increasing sales (Y) at Jelly Potter Jayasampurna Branch.